2021
DOI: 10.1002/ajmg.a.62355
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and respiratory infection in Down syndrome: A 10‐year cohort analysis of inpatient and outpatient encounters across the lifespan

Abstract: Respiratory illnesses are a significant contributor of morbidity and mortality among persons with Down syndrome (DS). Reviews have described respiratory illnesses of DS in childhood, but few have looked across the lifespan. Retrospective chart review of patients in our DS program with clinical encounters for respiratory illnesses from 2011 to 2020 was completed. Eighteen percent of clinical encounters were due to respiratory illnesses. Of these, 120 were seen in the emergency department, 88 were admitted, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In this review of claims data from 1,739,549 patients from 825 hospi- PNA is not surprising (Blake et al, 2021;Santoro et al, 2021). Indeed, our results align with previous studies, which have shown a 10-fold increased risk for COVID-19-related death in persons with DS (Clift et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this review of claims data from 1,739,549 patients from 825 hospi- PNA is not surprising (Blake et al, 2021;Santoro et al, 2021). Indeed, our results align with previous studies, which have shown a 10-fold increased risk for COVID-19-related death in persons with DS (Clift et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…In this review of claims data from 1,739,549 patients from 825 hospitals from January 2019 to June 2022, we found that the diagnosis of DS was associated with increased odds of mortality before and during the COVID‐19 pandemic. Respiratory infections are a known leading cause of mortality in patients with DS, and mortality from COVID‐19 PNA is not surprising (Blake et al, 2021; Santoro et al, 2021). Indeed, our results align with previous studies, which have shown a 10‐fold increased risk for COVID‐19‐related death in persons with DS (Clift et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Children with DS are at an increased risk of severe pneumococcal infections (Blake et al, 2021); lower respiratory tract infections are the leading cause of acute hospital admission, and the predominant cause of ICU admissions in children with DS is pneumonia (Ram & Chinen, 2011). Children with DS have a 12 times increased risk of mortality when infected with pneumonia compared to children without DS (Ram & Chinen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Children with DS have been shown to be at increased risk of severe pneumococcal infections (Blake et al, 2021). Pneumonia has been found to be the most common cause of hospital admissions, and the most common indication for the pediatric intensive care unit (ICU) admission for children with DS (Hilton et al, 1999; Santoro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because of immune disturbances, Down syndrome patients are more susceptible to respiratory tract infections and acute respiratory distress syndrome (ARDS) ( 6 ). Congenital heart defects and respiratory infections remain the most common causes of death and hospitalization among persons with Down syndrome ( 7 , 8 ). In children with Down syndrome, < 80% of all hospitalizations and intensive care unit (ICU) admissions result from lower respiratory tract infections, and < 29% of deaths are associated with pneumonia, influenza, and aspiration ( 9 ).…”
mentioning
confidence: 99%